PENERAPAN MODEL INQUIRY LEARNING BERBANTUAN MEDIA INTERAKTIF CANVA UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Eka Setyaning Marsudi Utami; Rusnilawati Rusnilawati; Rini Laksana Trisnowati (STKIP Subang, 2024)
The purpose of this research is to enhance student learning outcomes in mathematics education for first-grade elementary school students. This study employs classroom action research (CAR). Data collection methods involve evaluating student learning outcomes through tests. Descriptive analysis is used to analyze the acquired data. The research findings conclude that learning outcomes have improved. In the pre-cycle, the average class score was 62. Meanwhile, in Cycle I, the average class score increased to 78, and in Cycle II, it further improved to an average of 86. Thus, it can be inferred that the implementation of the Inquiry Learning model, assisted by interactive media Canva, enhances student learning outcomes in mathematics during the teaching and learning process at SDN Bratan 2.